Comprehensive Physiology 2017
DOI: 10.1002/cphy.c160044
|View full text |Cite
|
Sign up to set email alerts
|

C1q/TNF‐Related Protein 3 (CTRP3) Function and Regulation

Abstract: As the largest endocrine organ, adipose tissue secretes many bioactive molecules that circulate in blood, collectively termed adipokines. Efforts to identify such metabolic regulators have led to the discovery of a family of secreted proteins, designated as C1q tumor necrosis factor (TNF)-related proteins (CTRPs). The CTRP proteins, adiponectin, TNF-alpha, as well as other proteins with the distinct C1q domain are collectively grouped together as the C1q/TNF superfamily. Reflecting profound biological potency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 88 publications
(182 reference statements)
5
88
0
Order By: Relevance
“…The major significant finding of this study is that almost all circulating CTRP3 in humans is found as either the MMW or HMW oligomer. This finding supports previous speculation that the oligomer conformation of CTRP3 is important for its functional activity (Li et al, ; Peterson, ; Peterson et al, ). The secondary finding of this study is that total CTRP3 levels were almost identical between diabetic and nondiabetic populations (68.8 ± 20 vs. 70.7 ± 18 ng/ml), and there was no difference between these groups in circulating concentration of HMW or MMW CTRP3.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The major significant finding of this study is that almost all circulating CTRP3 in humans is found as either the MMW or HMW oligomer. This finding supports previous speculation that the oligomer conformation of CTRP3 is important for its functional activity (Li et al, ; Peterson, ; Peterson et al, ). The secondary finding of this study is that total CTRP3 levels were almost identical between diabetic and nondiabetic populations (68.8 ± 20 vs. 70.7 ± 18 ng/ml), and there was no difference between these groups in circulating concentration of HMW or MMW CTRP3.…”
Section: Discussionsupporting
confidence: 92%
“…Further, CTRP3 has been shown to be a potent insulin sensitizer and inhibits inflammation (Peterson et al, ), indicating that CTRP3 could play a major role in metabolic diseases such as obesity, nonalcoholic fatty liver disease, and type 2 diabetes. However, the associations between total CTRP3 levels with obesity or metabolic syndrome are controversial, as circulating CTRP3 levels have been shown to be elevated, decreased, or not changed with obesity (Li, Wright, & Peterson, ). These discrepancies indicate that the role of CTRP3 in human health is more complicated than can be identified by total circulating levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,29 CTRP-3 is an adipokine involved in adipogenesis and as a pleiotropic factor in metabolic and immunological processes which has been described to be inversely associated with BMI and metabolic syndrome. 31,32 Further being well-known for its anti-inflammatory properties, CTRP-3 thus resembles progranulin which has been described as an anti-atherosclerotic factor 33 and as an inhibitor of pro-inflammatory TNF signalling. 34,35 Similar to a potential inhibition…”
Section: Introductionmentioning
confidence: 99%
“…C1q tumor necrosis factor (TNF)‐related proteins (CTRPs) are a family of secretory cytokines with diverse metabolic and immunomodulatory functions . First identified in C3H10T1/2 mouse embryonic stem cells undergoing transforming growth factor‐β 1 (TGFβ1)‐induced chondrogenesis and associated with early cartilage condensations in developing mice, CTRP3 (alternately known as CORS26, cartducin, or cartonectin), a paralog of adiponectin, has been implicated in a wide variety of physiological processes ranging from obesity to reproductive function . Though its association with and function in growth plate cartilages have been acknowledged since its discovery, CTRP3 was not classically believed to function in bone tissue proper .…”
mentioning
confidence: 99%